ANALISIS PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN KONSUMEN TOKO KOSMETIK GAYA BARU - Zainuddin, Muh Zabir; Manan, La Ode ABdul; K, Sri Wahyuni (Fakultas Ekonomi Dan Bisnis Universitas Sulawesi Tenggara, 2021)
In the current era of globalization, providing good service satisfaction is an asset for organizations and companies, in realizing this desire is not easy, because many are playing in a company market, the tastes of one customer and another are also different, competition in all sectors the Indonesian economy, specially services that are very close to the community. The company will succeed in obtaining customers in numbers which, if judged to be able to provide service satisfaction for customers. Increased competition and the number of competitors that require business actors to always pay attention to the needs and desires of consumers and try to meet consumer expectations by providing more satisfying than what competitors do in improving service quality, according to Zeithaml and Bitner (2004), there are 5 dimensions of service quality. that must be considered include physical evidence, reliability (trust), responsiveness (responsiveness), assurance (guarantee), empathy (empathy). By paying attention to the 5 dimensions of service quality, it is expected that consumers will be satisfied. This study aims to determine the effect of service quality on customer satisfaction (a case study on a new style cosmetic shop in Baruga Market). This study uses quantitative methods, with a sample of 30 respondents. Data collection techniques: questionnaires and interviews. After the data is obtained, testing the data, presenting the data, and drawing conclusions. The results of this study indicate that service quality affects customer satisfaction, the better the service quality, the higher customer satisfaction.